Physical properties of Alaska pollock surimi gel as affected by emulsified level and heating rates - Van-Thi Nguyen; Emiko Okazaki (Fisheries and Aquatic Sciences)
Recently, there has been increased concern about adding fish oil to surimi to enhance its functionality in products derived from it. Our previous study showed that emulsification somewhat improves surimi’s gel-formation capacity. Additionally, as lipids are electrical insulators and ohmic heating (OH) has become more popular lately, it will be important to confirm how the emulsified lipid affects the gel-forming property. This study examines the quality and heating properties of surimi gels, utilizing OH at varying heating speeds to investigate the effects of mixing oil with emulsified surimi gel. Frozen Alaska pollock surimi (RA grade) was diced, mixed with ice water and 1.5% salt, and then blended with refined fish oil (10%) under four different mixing conditions to produce different levels of emulsified surimi paste. The produced surimi pastes were placed within the casing tubes, and two methods were employed to create the heat-induced gel: OH (applied at two different heating speeds: 3°C /min [slow] and 80°C/min [fast]) and water bath heating (heating samples to 90°C for 30 min). Physical variables such as color, water holding capacity (WHC), rheological characteristics, microstructural features, and physical attributes were used to evaluate the effects of electrical factors and oil particle dispersion on the gel qualities. The means were compared using Fisher’s multiple range test. The findings showed that the emulsification of fish oil into surimi promoted gel properties in both water bath heating and OH. High-speed mixing (vigorous mixing) reduced the size of oil droplets, produced uniform and stable emulsified surimi paste, and contributed to the higher gel strength. Heating rate also influenced the gel properties and significantly improved the gel-forming ability and WHC of emulsified surimi paste. The highest breaking strength and lowest drip loss of emulsified gels were obtained by a slow heating rate (3°C/min) in comparison with the other conditions (p < 0.05). Rheological and color measurements also showed coincident results. These findings may have crucial implications for producing high-quality surimi-based products.